Reading about the SYK model I encounter a trick that should help to calculate the thermal entropy of the system. I am not able to understand what they are doing though. Particularly the part from eq.135 to eq.137 of Gabor Sarosi is giving me problems. My attempt to understand this part:

$$e^{-\beta F}=Z\sim e^{-NI[G_*,\Sigma_*]}$$


$I[G,\Sigma]=-\frac{1}{2}\log\det[\partial_{\tau}-\Sigma]+\frac{1}{2}\int\int d\tau d\tau'\left(\Sigma(\tau,\tau') G(\tau,\tau')-\frac{1}{q}J^2G(\tau,\tau')^q\right)$

Since we don't want to deal with the determinant we write

\begin{equation} \begin{split} J\partial_J\left(-\frac{\beta F}{N}\right)&=J\partial_J(-I)\\ &=\frac{J^2}{q}\int\int_0^\beta d\tau'd\tau G_*(\tau,\tau')^q\\ &=\frac{\beta J^2}{q}\int_0^\beta d\tau G_*(\tau)^q \end{split} \end{equation}

Where in the last step I used translational invariance $G(\tau,\tau')=G(\tau-\tau')$. I use the Swinger-Dyson equations

\begin{split} &G(i\omega_n)=[-i\omega_n-\Sigma(i\omega_n)]^{-1}\\ &\Sigma(\tau)=J^2G(\tau)^{q-1}. \end{split}

from this one gets that


Plugging this in to our integral gets us:

\begin{split} J\partial_J\left(-\frac{\beta F}{N}\right)&=\frac{\beta}{q}\int_0^\beta d\tau \Sigma(\tau)G(\tau)\\ &=\frac{1}{q}\sum_{\omega_n,\omega_m}\Sigma(i\omega_n)G(i\omega_m)\frac{1}{\beta}\int_0^\beta d\tau e^{-i\tau(\omega_n+\omega_m)}\\ &=\frac{1}{q}\sum_{\omega_n}\Sigma(i\omega_n)G(-i\omega_n)\\ &=-\frac{1}{q}\sum_{\omega_n}\Sigma(i\omega_n)G(i\omega_n)\\ &=\frac{1}{q}\sum_{\omega_n}(i\omega_n+G(i\omega_n)^{-1})G(i\omega_n)\\ &=\frac{1}{q}\sum_{\omega_n}i\omega_n G(i\omega_n)+\frac{1}{q}\sum_{\omega_n}1\\ &=-\frac{\beta}{q}\lim_{\tau\rightarrow0^+}\partial_\tau G(\tau)+\infty \end{split}

This is the point where I run in to trouble. Gabor Sarosi states that

$\frac{J^2\beta}{q}\int_0^\beta d\tau G(\tau)^q=-\frac{\beta}{q}\lim_{\tau\rightarrow0^+}\partial_\tau G(\tau)$

Why doesn't he have this infinite constant? Note that one can proof that $$\frac{\beta}{q}\lim_{\tau\rightarrow0^+}\partial_\tau G(\tau)=\frac{\beta}{N}\langle H \rangle$$ Is he absorbing the infinite constant into the energy somehow? Maybe using some sort of regularization scheme I am unaware of? Or did I just make a mistake? Hopefully one of you guy's can tell me what's going on here.


1 Answer 1


Moving my comment as an answer.

$$-\frac{\partial}{\partial \tau}G(\tau)-\int d\tau' \Sigma(\tau-\tau')G(\tau')= \delta(\tau) \xrightarrow[\delta(0^+)=0]{\tau \to 0^+} -\lim_{\tau \to 0^+}^{}\frac{\partial}{\partial \tau}G(\tau)-\int d\tau' \Sigma(0^+ -\tau')G(\tau') = 0.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.